IFPRI Malawi monthly maize market report, April 2025 - International Food Policy Research Institute; Benson, Anderson (International Food Policy Research Institute, 2025)
Retail prices of maize fell by 21% in April due to the arrival of newly harvested maize on the market. Relatively cheap imports from all three neighboring countries contributed to the decline in maize prices. Maize retailed below the government-mandated price in 21 out of 26 monitored markets.